PERENCANAAN STRATEGI HOSHIN KANRI DAN BALANCE SCORECARD PADA PERUSAHAAN DISTRIBUTOR - Daniel Marcello Langelo; Carla Olyvia Doaly; Helena Juliana Kristina (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2022)
Strategic planning can facilitate the company in achieving its targets and objectives where there is a consolidation of the company's strategic plan. PT. XYZ is a distributor business that sells various local products. During the covid-19 period, the Company experienced a decline in performance of 11% seen from 2019 sales results of 155,306 product units while in 2020 it was 138,286 product units. For this reason, it is necessary to strengthen the strategy implemented by the company starting from measuring performance to find out the root of the company's problems. Performance measurement is carried out through field observations and data collection through distributing questionnaires to employees who have worked for 2 years. The results are then processed using the Balanced Scorecard (BSC) approach, namely the translation of the vision and mission which is divided into 4 perspectives, namely Finance, Customers, Internal Business Processes, and Learning and Growth. The weight of each perspective is 0.318, 0.229, 0.175, and 0.278, respectively. This study resulted in 12 Key Performance Indicators (KPI) and then processed using the Objective Matrix (OMAX) and the Traffic Light System assessment system. There are 4 performance indicators that are good, 3 performance indicators that have not been achieved, and 5 indicators of poor performance. To overcome this condition, Hoshin Kanri's integration strategy planning is carried out by identifying the company's goals, targets, and actions that need to be taken to strengthen the company's condition. Through these proposals and strategic planning, it is expected that the company will gain a 13% increase in profits.